The N-terminal region of the human immunodeficiency virus envelope glycoprotein gp120 contains potential binding sites for CD4. - Syu, W J (1990)
Human immunodeficiency virus (HIV) vaccines targeted at blocking HIV-CD4 interactions are expected to be less affected by the sequence heterogeneity of HIV than those targeted at variable regions of the envelope outercoat glycoprotein, gp120. All potential CD4 binding sites identified thus far in HIV are localized in the C-terminal region of gp120. In this study we demonstrate that the N-terminal region of gp120 also contains conserved residues critical for binding to CD4 and that gp120-CD4 interactions can be blocked by an antiserum with binding specificity to an N-terminal region of gp120. These results suggest that not all potential CD4 binding sites are present in the C-terminal region of gp120 and that an alternative HIV vaccine development strategy may have to include the N-terminal gp120 region as a component to raise effective CD4-blocking antibodies.